Corrosion behavior of NiTi alloys fabricated by laser powder bed fusion in relation to the formed passive films in Hank's solution - Yi-Fan Zhang; Liang-Yu Chen; Yong Liu; Hong-Yu Yang; Jin-Hua Peng; Chuanbo Zheng; Lina Zhang; Lai-Chang Zhang (Journal of Materials Research and Technology)
Laser powder bed fusion (L-PBF) produced NiTi alloys have significant potential in biomedical applications. Varying the parameters of the L-PBF process may result in the NiTi alloys with different ratios of B2 and B19′ phases, thereby, the different corrosion performance in the human body. However, a dearth of research efforts remains dedicated to resolving this issue. This work employed three different but comparable sets of parameters in the L-PBF process to produce NiTi alloys with different ratios of B2 and B19′ phases. The corrosion behavior of samples in Hank's solutions with the addition of lactic acid and their evolution of passive films were investigated. The sample with the dominant B2 phase has a slower passive film formation rate and a higher corrosion rate than those with mixed B2/B19′ phases at the early film formation stage. As corrosion progresses, the passive films rapidly form within 24 h, followed by gradual degradation, represented by their varied charge transfer resistance. The degradation of passive films is attributed to the dissolution of NiO on the film surfaces, resulting from the hydration reaction. Such a phenomenon leads to imperfections in the passive films, diminishing their protective effectiveness for the underlying substrate. The sample with a faster film formation rate would also maintain a considerable corrosion resistance after film degradation. The presence of lactic acid accelerates the degradation of passive film and decreases the corrosion resistance of samples. This work advances the understanding of the relationship between the evolution of passive films and the processing parameters of L-PBF-produced NiTi alloys.